1983
DOI: 10.1128/aem.46.2.297-303.1983
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gypsy Moth ( Lymantria dispar ) Nuclear Polyhedrosis Virus

Abstract: Characterization of the proteins and nucleic acid of the gypsy moth nuclear polyhedrosis virus isolated in Ithaca, N.Y. (LdNPV-IT) is presented. A total of 29 viral structural proteins were identified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis when the virus was isolated in the absence of alkaline protease activity. Fourteen surface envelope viral proteins were identified by lactoperoxidase iodination. Eleven proteins were associated with nucleocapsids prepared by Nonidet P-40 detergent treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The isolates can easily be distinguished from each other by the presence or absence of major and minor fragments resulting from digestion with either restriction enzyme. The restriction profiles for the LdMNPV-D isolate correspond to those published by other researchers (McCarthy et al 1979;Stiles et al 1983;Cusack and McCarthy 1989), whereas those for LdMNPV-H and LdMNPV-J have not previously been identified. DNA molecular weights were not determined in this study, although other researchers (Cusack and Mc-Carthy 1989;Riegel et al 1994;Kuzio et al 1999) have reported that the genome of isolates derived from Gypchek (which is the same as LdMNPV-D; Cunningham 1995) ranges from approximately 159 to 165 kb.…”
Section: Restriction Endonuclease Analysissupporting
confidence: 86%
“…The isolates can easily be distinguished from each other by the presence or absence of major and minor fragments resulting from digestion with either restriction enzyme. The restriction profiles for the LdMNPV-D isolate correspond to those published by other researchers (McCarthy et al 1979;Stiles et al 1983;Cusack and McCarthy 1989), whereas those for LdMNPV-H and LdMNPV-J have not previously been identified. DNA molecular weights were not determined in this study, although other researchers (Cusack and Mc-Carthy 1989;Riegel et al 1994;Kuzio et al 1999) have reported that the genome of isolates derived from Gypchek (which is the same as LdMNPV-D; Cunningham 1995) ranges from approximately 159 to 165 kb.…”
Section: Restriction Endonuclease Analysissupporting
confidence: 86%
“…This model work has implications for the in vivo chemistry hypothesized to underlie the antiviral activity of tannins against LdNPV. Specifically, cysteinyl residues on the LdNPV envelope proteins rather than lysyl or histidyl alternatives are the likely loci for covalent modification by galloyl-derived orthoquinoid electrophiles in the GM midgut. Experiments to test this premise are ongoing.…”
Section: Resultsmentioning
confidence: 99%
“…Insects are probably subject to as wide a variety of diseases. A number of pathogenic microorganisms -viruses, bacteria, fungi, and microsporidia (for example: Lymantria dispar nucleopolyhedrosis virus, Bacillus thuringiensis Berliner, Entomophaga maimaiga Humber, Shimazu & Soper, Nosema lymantriae (Weiser), Nosema serbica Weiser) -infect the gypsy moth (Pilarska and Vávra, 1991;Sidor, 1979;Stiles et al, 1983;Tabaković-Tošić, 2008;Tabaković-Tošić et al, 2011a,b;Weiser, 1998). The epizootics of them are often spectacular, and mortality is most prevalent during gypsy moth outbreaks.…”
Section: Resultsmentioning
confidence: 99%